Speciation on the Rocks: Integrated Systematics of the Heteronotia spelea Species Complex (Gekkota; Reptilia) from Western and Central Australia - Pepper, Mitzy; Doughty, Paul; Fujita, Matthew K.; Moritz, Craig; Keogh, J. Scott (PloS one, 2013)
The isolated uplands of the Australian arid zone are known to provide mesic refuges in an otherwise xeric landscape, and divergent lineages of largely arid zone taxa have persisted in these regions following the onset of Miocene aridification. Geckos of the genus Heteronotia are one such group, and have been the subject of many genetic studies, including H. spelea, a strongly banded form that occurs in the uplands of the Pilbara and Central Ranges regions of the Australian arid zone. Here we assess the systematics of these geckos based on detailed examination of morphological and genetic variation. The H. spelea species complex is a monophyletic lineage to the exclusion of the H. binoei and H. planiceps species complexes. Within the H. spelea complex, our previous studies based on mtDNA and nine nDNA loci found populations from the Central Ranges to be genetically divergent from Pilbara populations. Here we supplement our published molecular data with additional data gathered from central Australian samples. In the spirit of integrative species delimitation, we combine multi-locus, coalescent-based lineage delimitation with extensive morphological analyses to test species boundaries, and we describe the central populations as a new species, H. fasciolatus sp. nov. In addition, within the Pilbara there is strong genetic evidence for three lineages corresponding to northeastern (type), southern, and a large-bodied melanic population isolated in the northwest. Due to its genetic distinctiveness and extreme morphological divergence from all other Heteronotia, we describe the melanic form as a new species, H. atra sp. nov. The northeastern and southern Pilbara populations are morphologically indistinguishable with the exception of a morpho-type in the southeast that has a banding pattern resembling H. planiceps from the northern monsoonal tropics. Pending more extensive analyses, we therefore treat Pilbara H. spelea as a single species with phylogenetic structure and morphological heterogeneity.